Trouble spots in taxation : essays in the philosophy of taxation and other public finance problems - Groves, Harold M. (Harold Martin), 1897-1969 (Taft Memorial Fund lectures, 1948)
An informal discussion for the general reader of the most critical problems of taxation, including an important chapter on the income tax. Originally published in 1948. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.